Investigations of the scoring perspectives for snowboard big air based on interview and evaluation survey - Tsubaki, Y.; Ozaki, H.; Kawano, Y.; Zippo, K.; Yokozawa, T. (Frontiers in Sports and Active Living, 2026)
Introduction: